ANALISIS LITERASI KEUANGAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Suryanto, Suryanto; Rasmini, Mas (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2018)
This study aims to analyze financial literacy and find out the factors that influence the financial literacy ofmicro, small and medium enterprises (MSMEs) in the city of Bandung. This study uses a quantitativeapproach to the type of verification research. Primary data is obtained through the distribution ofquestionnaires to MSMEs players in the city of Bandung. The sampling technique uses proportional randomsampling with a sample size of 30 respondents. Other data is obtained through library observation andstudy. The analysis technique used is multiple linear regression. The results showed that the financialliteracy of SMEs in the city of Bandung was in the medium category. There are several factors thatsimultaneously influence financial literacy, namely age, formal education level, and business income. Whilepartially only the formal education level and business income that influences the level of financial literacy.While age does not have an effect on the level of financial literacy.